Perspectives on Involuntary Treatment of Anorexia Nervosa - Clausen, Loa (Frontiers in Psychiatry, 2020)
Involuntary treatment of anorexia nervosa is an option in cases in which the patient’s life or other people’s lives are at risk or, in some countries, to prevent the deterioration of the illness. Involuntary treatment is often regarded as controversial and has been intensely debated, although typically with few references to documented knowledge. This paper provides a research perspective of the topic by examine data in the field of the involuntary treatment of anorexia nervosa to pinpoint present knowledge as well as areas demanding clinical action or research attention. The prevalence of involuntary treatment in general as well as specific measures is described and possible early markers of patients at risk of involuntary treatment are discussed. Studies including patients’ perspectives of involuntary treatment show the complexity of this treatment, its initiation, and its consequences. To qualify future discussions, improve current practice, and minimize involuntary treatment in general as well as on an individual level, at least four areas need attention: (i) the present specific symptoms of anorexia nervosa and their imminent consequences, (ii) illness history, (iii) overall psychiatric symptoms and general functioning, and (iv) contextual sphere of the patient. In particular, the last two require attention from both clinicians and researchers. Furthermore, critical evaluation of the attitudes of both patients and health care professionals towards each other and the treatment is recommended.